Regulatory Incentives and the Thrift Crisis: Dividends, Mutual-to-Stock Conversions, and Financial Distress. - Kroszner, Randall S; Strahan, Philip E (Journal of Finance, 1996)
During the 1980s, insolvency of individual thrifts and the thrift deposit insurer created severe incentive problems. Lacking cash to close insolvent thrifts, regulators induced nearly $10 billion of private capital to flow into the industry through mutual-to-stock conversions. The authors test a theory of how regulators encouraged capital-impaired mutual thrifts to convert by permitting them to pay dividends rather than rebuild capital. They estimate the costs of this policy and interpret the 1991 Federal Deposit Insurance Corporation Improvement Act as requiring regulators to impose restraints on depository institutions parallel to debt covenants that prevent capital distributions by nonfinancial firms experiencing distress.